2016
DOI: 10.1108/cpoib-10-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

From margin to center: listening to silenced subjectivities in international business

Abstract: Purpose The editorial introduces the special issue entitled, “Voices at/from the margins: Articulating the consequences of international business”. Design/methodology/approach The editorial begins by briefly describing how the idea for the special issue was initiated and then provides an overview of the articles included. Findings The editorial contains a discussion of the themes emerging from the special issue articles. Originality/value The editorial provides some consideration of how the collection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Interestingly, there are complex reasons why the CSR cases in developing economies are at odds with those of industrialized nations. The issue of defining what constitutes good management practices revolves around an array of deep-rooted questions of designed institutional deficiencies, socio-economic disequilibrium, environmental turbulence [10,11], historical bias, and academic hegemony [12][13][14][15]. CSR broadly refers to the organization's socio-economic, legal, ethical, and discretionary obligations toward society and the environment [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there are complex reasons why the CSR cases in developing economies are at odds with those of industrialized nations. The issue of defining what constitutes good management practices revolves around an array of deep-rooted questions of designed institutional deficiencies, socio-economic disequilibrium, environmental turbulence [10,11], historical bias, and academic hegemony [12][13][14][15]. CSR broadly refers to the organization's socio-economic, legal, ethical, and discretionary obligations toward society and the environment [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We note that some have suggested that the notion of "career" may be emblematic of dominant Western/Global North representations of individuals striving for professional success and may not apply to career logics in other contexts, particularly in the Global South (e.g. Prasad and Durepos, 2016). The findings from our study provide evidence to the contrary; that exploring the local workers' career trajectories-their motivations, transitions and experiences within a highly internationalized service sector-may provide important insights about the very notion of success and its subjective internalization.…”
Section: Discussionmentioning
confidence: 98%
“…How do the behaviours of MNEs and local firms in response to industry declines in EEs affect by national and international political dynamics and vice versa? Research by IB scholars on declining industries in EEs from the vantage point of these perspectives can contribute to a broad discourse on IB research into marginalised subjects (Durepos et al , 2016; Prasad and Durepos, 2016). Methodological innovations, such as global ethnography (Burawoy, 2001), should be able to provide powerful tools for research in these endeavours.…”
Section: Discussionmentioning
confidence: 99%